Produção de biossurfactante e aplicação na remedição de ambientes contaminados por metais pesados. - Silva, Renata Raianny da (2022)
Soil contamination by heavy metals is a result of different industrial activities, and can cause environmental risks such as contamination of biological systems and the subsoil through the leaching process, various disorders and diseases in humans if they enter the ecosystem due to their high toxicity. Due this reality, the development of new technologies to remediate the generated contaminants becomes increasingly urgent. Biosurfactants consist of secondary metabolites from bacteria, yeasts and filamentous fungi. Considering the potential of yeast from Candida genera to produce non-toxic and biodegradable surfactants, this work aimed at the production of a low-cost biosurfactant produced by Candida bombicola URM3718 and application in the remediation of environments contaminated by heavy metals. The first invention refers to the biosurfactant production process by C. bombicola, using agro-industrial residues (molasses, corn steep liquor and residual soybean oil). The second invention refers to the potential application of the Bioproduct (Bombisan) in the removal of heavy metals. Tests for the stability of the surface tension and emulsification index of the Bioproduct were carried out under extreme conditions of temperatures (0°C, 5°C, 70°C, 100°C and 120°C), pH (2-12) and concentrations of NaCl (2 – 12) demonstrating the stability of Bombisan. The Bioproduct was characterized as being an anionic molecule of polymeric nature and non-toxic. It showed potential for heavy metals removal in contaminated soil, under dynamic conditions, showed removal of Fe, Zn and Pb with percentages between 70 and 88 %, while the highest removal of Pb was 48 %. Tests on packed columns also confirmed the ability of the Bioproduct to remove Fe, Zn and Pb, between 40 and 65 %. The removal kinetics showed an increasing percentage, reaching removal of 50, 70 and 85% for Pb, Zn and Fe, respectively, reaching a higher removal efficiency at the end of 24 hours. The biosurfactant was also able to significantly reduce the electrical conductivity of solutions containing heavy metals. The Bioproduct (Bombisan) has potential for application in industrial processes to remediate soils and effluents polluted by inorganic contaminants.